Perspectives of Persons With Arthritis on the Use of Wearable Technology to Self Monitor Physical Activity: A Qualitative Evidence Synthesis. Issue 9 (27th May 2022) - Leese, Jenny; Geldman, Jasmina; Zhu, Siyi; Macdonald, Graham G.; Pourrahmat, Mir‐Masoud; Townsend, Anne F.; Backman, Catherine L.; Nimmon, Laura; Li, Linda C.
Abstract : Objective: We aimed to broaden understanding of the perspectives of persons with arthritis on their use of wearables to self‐monitor physical activity, through a synthesis of evidence from qualitative studies. Methods: We conducted a systematic search of 5 databases (including Medline, CINAHL, and Embase) from inception to 2018. Eligible studies qualitatively examined the use of wearables from the perspectives of persons with arthritis. All relevant data were extracted and coded inductively in a thematic synthesis. Results: Of 4, 358 records retrieved, 7 articles were included. Participants used a wearable during research participation in 3 studies and as part of usual self‐management in 2 studies. In remaining studies, participants were shown a prototype they did not use. Themes identified were: 1) the potential to change dynamics in patient–health professional communication: articles reported a common opinion that sharing wearable data could possibly enable patients to improve communication with health professionals; 2) wearable‐enabled self‐awareness, whether a benefit or downside: there was agreement that wearables could increase self‐awareness of physical activity levels, but perspectives were mixed on whether this increased self‐awareness motivated more physical activity; 3) designing a wearable for everyday life: participants generally felt that the technology was not obtrusive in their everyday lives, but certain prototypes may possibly embarrass or stigmatize persons with arthritis. Conclusion: Themes hint toward an ethical dimension, as participants perceive that their use of wearables may positively or negatively influence their capacity to shape their everyday self‐management. We suggest ethical questions pertinent to the use of wearables in arthritis self‐management for further exploration.